Międzywyznaniowe kontakty językowe. "Sacrum i profanum" w reformacyjnej polemice religijnej = Language contacts among Christian denominations. "Sacrum and profanum" in the reformation religious polemics - Hawrysz, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present considerations are based on the analysis of the 16th century texts of religious polemics by Marcin Czechowic, the leader of the Polish Brethren, and his adversaries: Marcin Łaszcz, Hieronim Powodowski and Kasper Wilkowski, which evidence not only the erudition of the religious debates but also highly emotional linguistic behaviour.
Keywords: polemika; komunikacja polemiczna; bracia polscy; jezuici; agresja językowa; strategia abominacyjna; Czechowic, Marcin (1532-1613); polemic; polemical communication; Polish Brethren; Jesuits; language aggression; abomination strategy